2007
DOI: 10.1111/j.1365-3040.2007.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm in leaf‐level photosynthesis: direct and diffuse lights are not equal

Abstract: Global-change scenarios suggest a trend of increasing diffuse light due to expected increases in cloud cover. Canopy-level measurements of plant-community photosynthesis under diffuse light show increased productivity attributed to more uniform distribution of light within the forest canopy, yet the effect of the directional quality of light at the leaf level is unknown. Here we show that leaflevel photosynthesis in sun leaves of both C3 and C4 plants can be 10-15% higher under direct light compared to equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 36 publications
7
97
1
3
Order By: Relevance
“…However, the thin shade leaf approached its photosynthetic capacity beyond 750 mmol m 22 s 21 PPFD. Previously observed data by Brodersen et al (2008) are also shown in Figure 5 for comparison.…”
Section: Modeled Leaf-level Photosynthetic Light Response Curvessupporting
confidence: 57%
See 3 more Smart Citations
“…However, the thin shade leaf approached its photosynthetic capacity beyond 750 mmol m 22 s 21 PPFD. Previously observed data by Brodersen et al (2008) are also shown in Figure 5 for comparison.…”
Section: Modeled Leaf-level Photosynthetic Light Response Curvessupporting
confidence: 57%
“…While the reasons for this discrepancy are unclear, it is possible that the sun-and shade-grown leaves differentially incurred photoinhibition due to excess light absorption during the light acclimation period. Specifically, Brodersen et al (2008) acclimated both sets of leaves at 500 mmol m 22 s 21 , which would likely induce different degrees of photoinhibition for the sun-grown versus shade-grown leaf. Without spatially resolved data on the degree of nonphotochemical quenching throughout each leaf, however, we cannot be certain of the mechanism underlying these apparent differences in light-limited f PSII between sun-grown and shade-grown leaves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Canopy-level measurements of photosynthesis under diffuse light show increased productivity attributed to more uniform distribution of light within a forest canopy. Brodersen et al (2008) show that leaf-level and canopy-level photosynthetic processes react differently to the directionality of light, and increases in canopy-level photosynthesis occur even though leaf-level photosynthesis decreases under diffuse light. It is important to study regional haze in China on climate and crop production.…”
Section: Uncertainty Of the Modelingmentioning
confidence: 99%